Go Rural!! Hinterland - Challenges, Insights, Opportunities and Strategies - Gaikwad, Vinod S. (Indian Journal of Marketing, 2010)
India Inc. is witnessing an emerging paradigm shift in rural marketing. India has traditionally been an agrarian economy. Agriculture contributed to more than 50% of the GDP in 60s. The result - even though global economy was witnessing down turn in demand, India's rural economy remained virtually unscathed, in part due to the country's almost autonomous agriculture sector. Agriculture sector is at the very core of the rural economic prosperity along with other sectors like FMCG, consumer durables etc. Since ages, various rural development programs have been run by corporates. Rural sector was the only one which withstood the global economic down turn and continues to grow. For many companies, rural market contributed almost 50% of their total sales revenue. Companies have well realized that if growth is the only option, rural market is the only way to grow ahead. And the organizations who that take initial steps and leaps in the approach will benefit from the first mover advantage, gain brand loyalty and better business growth. However, the rural market has always been affected by agricultural performance based on marginal land holdings, dependence on unpredictable monsoons and still existing primitive and traditional ways of farming due to marginal land holdings. The rural market in India brings in bigger revenues in the country, as the rural regions comprise of the maximum consumers in this country. The rural market in Indian economy generates almost more than half of the country's income.